Isolation of Leptospira javanica from sheep - Natarajaseenavasan, K; Ratnam, S (The Indian Journal of Animal Sciences, 2012)
Attempts were made to isolate leptospires from the kidneys of sheep and goats of slaughterhouse. An isolate S5 was made from sheep kidney and identified as serovar javanica by monoclonal antibody technique. The seroprevalence in slaughtered sheep and goats was 59% and 80%, respectively. The slaughterhouse workers had a seroprevalence of 80% whereas only 14% of the human controls were seropositive. Serogroup Australis predominated in sheep (19%) and slaughterhouse workers (36%) whereas Javanica was the common serogroup in the goats. Isolation of Leptospira serovar javanica is the first report in India.